Prevalence of thyroid disorders among pregnant women in lower Assam - Diganta Das; Syed Javed Salman Chisty; Karabi Barman (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: Prevalence of thyroid disorders during pregnancy has a wide geographic variation. There is paucity of data on prevalence of thyroid disorders in Indian pregnant women. Lower Assam consists of people of different culture and ethnicity. In a pilot study done in lower part of Assam among 1st trimester pregnant lady in which the prevalence was alarmingly high. Objective: The objective of the study is to find out prevalence of thyroid disorders among pregnant women in lower Assam. Materials and methods: The study was an out patient department (OPD) based randomized, prospective cohort, observational study over a period of one year. The 880 pregnant women between the age group of 18 to 45 years, who were attending the antenatal OPDs of Fakhruddin Ali Ahmed Medical College, were included in the study. Results: The mean age and thyroid stimulating hormone (TSH) level of study population was 23.70 ± 4.77 years and 2.83±4.02 mIU/ml respectively. The prevalence of thyroid dysfunction was 62.72%. Of this, prevalence of hypothyroidism was 61.70% and that of hyperthyroidism was 1.02%. The majority of the pregnant lady in their 1st trimester was suffering from hypothyroidism (58.6%) (TSH level 2.8± 3.2 mIU/). The prevalence of hypothyroidism is more in pregnant ladies whose age more than 30 yrs (63.8 %). Conclusion: In our study we found that more than 58.6% pregnant women in their first trimester were suffering from hypothyroidism. Thyroid disorders are common in pregnancy, and the screening for thyroid dysfunction should be done early in pregnancy.